Alternating Hemiplegia of Childhood: A Series of Genetically Confirmed Four Cases from Southern India with Review of Published Literature - Bhardwaj, Naveen Kumar; Gowda, Vykuntaraju K.; Sardesai, Ashwin Vivek (Journal of Pediatric Genetics, 2020)
Alternating hemiplegia of childhood (AHC) is a rare autosomal dominant neurodevelopmental disorder with mutation on ATP1A3 gene. Delay in diagnosis and inappropriate diagnosis are common. In this article, we described four genetically confirmed AHC patients to provide an improved understanding of the disorder. First symptom in two patients was seizures and in other two patients was abnormal eye deviation. All had onset of plegic attacks within the first 18 months of their life. Tone abnormalities and movement disorders were present in all patients. Electroencephalogram was abnormal in two patients and all had normal magnetic resonance imaging of the brain. Response to treatment of plegic attacks was poor and also epilepsy was drug resistant. All cases had significant development delay and disability as of last follow-up. Although there is no effective treatment so far, early diagnosis is required to avoid unnecessary treatment.
Keywords: alternating hemiplegia of childhood; plegic attacks; ATP1A3 gene